Modified Laparoscopic Inverted Triangle Model for Extended Lesion Resection in the Treatment of Symptomatic Localized Adenomyosis in Women Who Have Completed Childbirth - Libing Liu; Weiwei Wei; Huimin Tang; Yao Chen; Hong Zheng; Bin Tang; Ruxia Shi; Jiming Chen; Bairong Xia; Bingying Lu (Clinical and Experimental Obstetrics & Gynecology)
Background: To evaluate the clinical efficacy and safety of the modified laparoscopic inverted triangle model for extended lesion resection in treating dysmenorrhea focal adenomyosis in women who have completed childbirth. Methods: A total of 52 patients with dysmenorrhea focal adenomyosis treated in the Department of Gynecology of the Affiliated Changzhou Second People’s Hospital of Nanjing Medical University from July 2014 to August 2020 were retrospectively analyzed. They underwent the modified laparoscopic inverted triangle model for extended lesion resection. The scope of resection included the focal adenomyosis lesions and along with part of the surrounding normal myometrial tissue and endometrium in order to ensure full resection of adenomyosis lesions without residual. Surgical outcome and adverse effects on ovarian functions were evaluated through the retrospective analysis compared the changes of dysmenorrhea visual analog scale (VAS) score changes, uterine volume changes, changes in serum CA125 level, and serum anti-mullerian hormone (AMH) level changes prior to surgery as well as 3, 6, 12, and 24 months after surgery. Results: All operations were completed by laparoscopy without conversion to laparotomy. No serious complications occurred during or after surgery. The dysmenorrhea VAS score, uterine volume, and serum CA125 level at 3, 6, 12, and 24 months after surgery were significantly lower than baseline and the difference was statistically significant. The serum AMH level showed a downward trend 3 months after surgery compared with the pre-surgery level, but the difference was not statistically significant (p = 0.27). The response rates at 3, 6, 12, and 24 months after surgery were 98.1%, 98.1%, 96.1%, and 88.5%, respectively, and the complete response rates were 30.8%, 34.6%, 34.6%, and 21.1%, respectively. Conclusions: Modified laparoscopic inverted triangle model for extended lesion resection is a safe and effective conservative surgical method for treating dysmenorrhea focal adenomyosis.